Genetic associations of visual scores with subsequent rebreeding and days to first calving in Nellore cattle - Boligon, A. A. [UNESP]; Ayres, D. R. [UNESP]; Pereira, R. J. [UNESP]; Morotti, N. P. [UNESP]; Albuquerque, Lucia Galvão de [UNESP] (Wiley-Blackwell, 2012)
Records of Nellore animals born from 1990 to 2006 were used to estimate genetic correlations of visual scores at yearling (conformation, C; finishing precocity, P; and muscling, M) with primiparous subsequent rebreeding (SR) and days to first calving (DC), because the magnitude of these associations is still unknown. Genetic parameters were estimated by multiple-traits Bayesian analysis, using a nonlinear (threshold) animal models for visual scores and SR and a linear animal models for weaning weight (WW) and DC. WW was included in the analysis to account for the effects of sequential selection. The posterior means of heritabilities estimated for C, P, M, SR and DC were 0.24 +/- 0.01, 0.31 +/- 0.01, 0.30 +/- 0.01, 0.18 +/- 0.02 and 0.06 +/- 0.02, respectively. The posterior means of genetic correlations estimated between SR and visual scores were low and positive, with values of 0.09 +/- 0.02 (C), 0.19 +/- 0.03 (P) and 0.18 +/- 0.05 (M). on the other hand, negative genetic correlations were found between DC and C (-0.11 +/- 0.09), P (-0.19 +/- 0.09) and M (-0.16 +/- 0.09). The primiparous rebreeding trait has genetic variability in Nellore cattle. The genetic correlations between visual scores, and SR and DC were low and favourable. The genetic changes in C, P and M were 0.02, 0.03 and 0.03/year, respectively. For SR and DC, genetic trends were 0.01/year and -0.01 days/year, respectively, indicating that the increase in genetic merit for reproductive traits was small over time. Direct selection for visual scores together with female reproductive traits is recommended to increase the fertility of beef cows.
Keywords: Bayesian inference; Beef cattle; conformation; finishing precocity; muscling